Perubahan Perilaku Anak Prasekolah dalam Pemenuhan Asupan Gizi Seimbang melalui Penerapan PAUD Sadar Gizi di TK-IT Mutiara Hati Kota Semarang - Reni Pawestuti Ambari; Lita Latiana Lita; Khamidun Khamidun Khamidun (Pusat Penerbitan Universitas (P2U) Unisba, 2018)
The purpose of this study was to examine differences of preschool children's behaviour in fulfilment balanced nutritional intake through the program of